New developments and future challenges in prevention, diagnosis, and treatment of prosthetic joint infection. Issue 7 (31st January 2020) - Ricciardi, Benjamin F.; Muthukrishnan, Gowrishankar; Masters, Elysia A.; Kaplan, Nathan; Daiss, John L.; Schwarz, Edward M.
Abstract: Prosthetic joint infection (PJI) is a devastating complication that results in substantial costs to society and patient morbidity. Advancements in our knowledge of this condition have focused on prevention, diagnosis, and treatment, in order to reduce rates of PJI and improve patient outcomes. Preventive measures such as optimization of patient comorbidities, and perioperative antibiotic usage are intensive areas of current clinical research to reduce the rate of PJI. Improved diagnostic tests such as synovial fluid (SF) α‐defensin enzyme‐linked immunosorbent assay, and nucleic acid‐based tests for serum, SF, and tissue cultures, have improved diagnostic accuracy and organism identification. Increasing the diversity of available antibiotic therapy, immunotherapy, and alternative implant coatings remain promising treatments to improve infection eradication in the setting of PJI.